2007
DOI: 10.2134/jeq2006.0517
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Stream Water and Sediment Phosphorus among Select Ozark Catchments

Abstract: Stream sediments play a large role in the transport and fate of soluble reactive phosphorus (SRP) in stream ecosystems, and equilibrium P concentrations (EPC 0) of benthic sediments at which P is neither adsorbed nor desorbed are often related to stream water SRP concentrations. This study evaluated (i) the variation among water chemistry and sediment-P interactions among streams draining catchments that varied in the land use; (ii) the relations between SRP concentration, sediment EPC 0, and other measured ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 40 publications
6
71
1
Order By: Relevance
“…In fluvial systems (i.e., ditches/drainages and streams/rivers), built-up of sediment legacy P pools results from the deposition of particulate P as fluvial bed sediments (Ballantine et al, 2009), sorption of dissolved P onto riverbed sediments (Haggard et al, 2005(Haggard et al, , 2007Stutter et al, 2010) or onto suspended sediments that are subsequently deposited on the riverbed (Owens and Walling, 2002). Net N retention in sediment is mainly associated with the deposition of organic N, physical sorption, and biogeochemical interception (formation of organic N) by sediments in fluvial bed (Brunet and Astin, 1997;Noe and Hupp, 2005).…”
Section: Legacy Nutrient Dynamics In Sedimentsmentioning
confidence: 99%
“…In fluvial systems (i.e., ditches/drainages and streams/rivers), built-up of sediment legacy P pools results from the deposition of particulate P as fluvial bed sediments (Ballantine et al, 2009), sorption of dissolved P onto riverbed sediments (Haggard et al, 2005(Haggard et al, , 2007Stutter et al, 2010) or onto suspended sediments that are subsequently deposited on the riverbed (Owens and Walling, 2002). Net N retention in sediment is mainly associated with the deposition of organic N, physical sorption, and biogeochemical interception (formation of organic N) by sediments in fluvial bed (Brunet and Astin, 1997;Noe and Hupp, 2005).…”
Section: Legacy Nutrient Dynamics In Sedimentsmentioning
confidence: 99%
“…We know that nutrient concentrations in baseflow increase with anthropogenic influence within the catchment (Haggard et al, 2003(Haggard et al, , 2007Brion et al, 2010;Cox et al, 2013;Giovannetti et al, 2013). However, the landscape factors that likely are responsible for increased nutrients during baseflow also influence catchment hydrology.…”
Section: Watershed Management Using Baseflow Nutrient Concentrationsmentioning
confidence: 99%
“…Total phosphorus content of streambanks is also controlled by these factors (Palmer-Felgate et al, 2009), although the silt-clay content is often the largest driver (Bledsoe et al, 2000). Streambank phosphorus concentrations may also be higher in intensively farmed catchments (Palmer-Felgate et al, 2009) or in deforested areas (Haggard et al, 2007), although others have shown little correlation to land use (Nellesen et al, 2011;Tufekcioglu, 2010;Zaimes et al, 2008a).…”
Section: Phosphorus Loading and Bank Erosionmentioning
confidence: 99%